Exercise and well-being: Relationships with perceptions of exercise identity-behaviour consistency, affective reactions to exercise and passion. Issue 5 (3rd September 2019) - Guérin, Eva; Strachan, Shaelyn; Fortier, Michelle
Abstract : Exercise is strongly linked to well-being, although a better understanding of mechanisms underlying this relationship is needed. Concepts from Identity Theory and the Dualistic Model of Passion show promise in this area but have seldom been examined together. The goal of this exploratory study was to examine the relationships between perceptions of exercise identity-behaviour consistency (IBC), affective reactions to exercise, passion types and general well-being. The participants were 63 active Canadian adult women. Measures consisted of self-report questionnaires administered in the context of a larger study. Analyses involved hierarchical linear regressions and tests of indirect effects. Results showed that controlling for exercise levels, greater perceived consistency (IBC) was associated with higher levels of life satisfaction and vitality. Findings also revealed an indirect effect between extent of IBC and vitality through negative affect as well as an indirect effect on life satisfaction through positive affect. In regards to passion, there were significant interaction effects between passion types (harmonious, obsessive) and the extent of IBC in predicting vitality. For participants showing higher obsessive passion, vitality was poorer as the level of perceived behavioural consistency dropped. The results provide preliminary support in the exercise domain that behavioural verification of an endorsed identity can help promote broader emotional health. Moreover, rigid identification with the exerciser role is tied to needing to exercise to confirm one's identity and achieve greater well-being. Interventions should be geared towards helping individuals assimilate exercise into their view of themselves in a flexible and compassionate way.